Compact fiber laser at L-band region using Erbium-doped Zirconia fiber - Hamzah, Azura; Paul, Mukul Chandra; Harun, Sulaiman Wadi; Huri, N.A.D.; Lokman, Asiah; Pal, Mrinmay; Das, Swapan Kumar; Bhadra, Shyamal Kumar; Ahmad, Harith; Yoo, Seong Woo; Kalita, Mridu P.; Boyland, Alexander J.; et al. (IOP Publishing, 2011)
A compact Erbium-doped fiber laser (EDFL) operating in L-band region is demonstrated using a fabricated Erbium-doped Zirconia fiber (EDZF) for the first time. The fiber is fabricated by combining Zr and Al to achieve the maximum Erbium ion concentration of 4320 wt ppm. By using a fiber Bragg grating (FBG) in a ring configuration, the laser operates at 1579.6 nm with a slope efficiency of 13.6% and the threshold pump power of 25.1 mW. The lasing wavelength is obtained at Bragg wavelength with an output power of 13 dBm and a 3 dB spectral width of 0.02 nm using a piece of 2 m long EDZF in conjunction with 120 mW of 1480 nm pump power.